Analisis Strategi Pengembangan Usaha Kain Pada Usaha Mikro Kecil Dan Menenah (UMKM) Kota Binanga (Studi Kasus Toko Kain A.A Mahmud) - Dahrani Dahrani; Ropita Indah Siregar (Yayasan Rahmat Islamiyah, 2022)
This research was conducted to identify and analyze the strategy of developing the fabric business in the micro, small and medium enterprises of MSMEs in Binanga City, Kec. Barumun Tengah, Padang Lawas Regency. This research is descriptive in nature, namely research that aims to determine the development of the fabric business as the basis of the people's economy is something that needs to be followed up with real steps, by carrying out three strategies, namely management strategy, investment strategy and business strategy. The development of MSMEs needs to be destination directed at analyzing competitiveness, and formulating efforts to increase competitiveness in the context of developing competitiveness and the national economy, sharpening competitiveness is an effort that is in line with future competition. With a strategic location, promotions that can attract customers and sufficient capital will increase business development.